Improving Arabic Language Proficiency and Competence of Arabic Language Education Using AI Technology - Haniah Haniah; Hamka Ilyas; Nurwinanda; Harith Samae (Jurnal Al-Maqoyis, 2026)
Proficiency in Arabic is the main capital for those involved in the field of Arabic language education. Arabic lecturers and teachers who have high competence can make a positive contribution in developing quality curriculum, teaching methods, and teaching materials. The purpose of this study is to increase and analyze Arabic language competency (Maharah istima' and kalam) among Arabic language education class of Postgraduate UIN Alauddin Makassar using AI technology. The subjects of this study were students of Arabic Education Department of Master Programme at Postgraduate UIN Alauddin Makassar with the number of participants consisting of 11 students who chose the Maharat Lugawiyah course. The methods employed included tests, observations, surveys, and documentation. The study's findings are categorized according to the division of cycles in class action research and include the following information. The study occurred over two cycles, cycle I and cycle II, and the results showed that students experienced an increase from cycle I to cycle 2. The outcomes of this study show that postgraduate students at UIN Alauddin Makassar saw a considerable improvement in Arabic language acquisition as a result of the emergence of AI tools such as Duolingo, Easy Peasy, Busuu, and TalkPal. Virtual assistants and chatbots help students communicate directly, provide feedback, and encourage exercises that focus on maharah al-istima' and maharah kalam, allowing it to be an important achievement for the advancement and improvement of students' Arabic by employing technology as a learning platform.